2012
DOI: 10.1089/vim.2011.0052
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Spontaneous Clearance: Immunology and Genetic Variance

Abstract: Hepatitis C virus (HCV) infection is one of the most common chronic viral infections in the world. Approximately 80-90% of acutely infected individuals develop persistent infection, which is a major risk for liver cirrhosis and liver cancer. However, a small portion of patients (10-20%) clear the virus. Clinical outcomes of HCV infection are determined by the interplay between the host immune response, and viral and environmental factors. In regulating immune responses, cytokines play an indispensable role tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 75 publications
0
19
0
Order By: Relevance
“…In a meta-analysis of studies performed at different centers, it has been shown that there is no significant association between TNF-α-308, -238 gene polymorphisms and susceptibility to infection among different HCV subgroups. (30). Besides, the distributions of TNF-α-308, -238 A/G alleles were also not significantly different between the persistent infection group and the spontaneous clearance group.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In a meta-analysis of studies performed at different centers, it has been shown that there is no significant association between TNF-α-308, -238 gene polymorphisms and susceptibility to infection among different HCV subgroups. (30). Besides, the distributions of TNF-α-308, -238 A/G alleles were also not significantly different between the persistent infection group and the spontaneous clearance group.…”
Section: Discussionmentioning
confidence: 83%
“…Although one study compared ALT levels between SVR patients and non-responders and found no statistically significant difference (10), the other found a statistically significant difference between healthy controls and those with cirrhosis and hepatocellular carcinoma (30), these studies did not include TNF polymorphism. Abbas et al (41) studied HCV genotype 3 and found no association between ALT level and TNF-α-308 polymorphism.…”
Section: Discussionmentioning
confidence: 97%
“…Host immune response as a consequence of genetic background has been shown to play a crucial role in HCV infection pathogenesis and interindividual heterogeneity of disease outcomes (Amini & Poustchi 2012). Cytokine production varies among individuals and these variations are associated with SNPs located in the coding and promoter regions of cytokine genes (Ollier 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Dai et al (2006) suggested that the TNF polymorphism at position -308 may be a predictor of treatment failure in patients treated with a combination of IFN-α and RBV. However, studies conducted in the United States of America, Ireland and Japan have been unable to identify any association between TNF genetic polymorphisms and histological severity or response to antiviral therapy (Hohler et al 1998, Ollier 2004, Amini & Poustchi 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Multiple factors have been reported to affect the liver disease progression rate[4]. Single nucleotide polymorphisms (SNPs) in the non-coding or coding regions of cytokine genes have been documented to affect their expression and secretion, which can cause chronic inflammation and disease progression[5,6]. …”
Section: Introductionmentioning
confidence: 99%